Communication studies enter their sixties - Gudonienė, Vilija (Information & Media, 1996)
The article is devoted to the discussion on communication studies’ past, present and future. Multidisciplinarity of communication field sometimes is argued as a weakness, that causes the divergence of the studies. Some optimistical trends towards convergence are presented: self identification, institutionalization, communication scholars community and organizations, periodicals and textbooks.